Analysis of Community Empowerment Through the Earth Alms Tradition in Cantigi Kulon Village, Cantigi District, Indramayu Regency - Siti Juhrotun Hasanah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The tradition of